The developing ovary of the South American plains vizcacha, Lagostomus maximus (Mammalia, Rodentia): Massive proliferation with no sign of apoptosis-mediated germ cell attrition - Leopardo, Noelia Paola (2011)
Apoptosis-dependent massive germ cell death is considered a constitutive trait of the developing mammalian ovary that eliminates 65-85% of the germinal tissue depending on the species. After birth and during adult lifetime, apoptotic activity moves from the germ cell proper to the somatic compartment, decimating germ cells through follicular atresia until the oocyte reserve is exhausted. In contrast, the South American rodent Lagostomus maximus shows suppressed apoptosis-dependent follicular atresia in the adult ovary, with continuous folliculogenesis and massive polyovulation, which finally exhausts the oocyte pool. The absence of follicular atresia in adult L. maximus might arise from a failure to move apoptosis from the germinal stratum to the somatic compartment after birth or being a constitutive trait of the ovarian tissue with no massive germ cell degeneration in the developing ovary. We tested these possibilities by analysing oogenesis, expression of germ cell-specific VASA protein, apoptotic proteins BCL2 and BAX, and DNA fragmentation by TUNEL assay in the developing ovary of L. maximus. Immunolabelling for VASA revealed a massive and widespread colonisation of the ovary and proliferation of germ cells organised in nests that disappeared at late development when folliculogenesis began. No sign of germ cell attrition was found at any time point. BCL2 remained positive throughout oogenesis, whereas BAXwas slightly detected in early development. TUNEL assay was conspicuously negative throughout the development. These results advocate for an unrestricted proliferation of germ cells, without apoptosis-driven elimination, as a constitutive trait of L. maximus ovary as opposed to what is normally found in the developing mammalian ovary.